Upaya Peningkatan Pengetahuan Anak Sekolah Dasar terhadap Logo dan Expire Date Obat - Hifdzur Rashif Rija'i; Nanda Silvana Alfin; Nur Dwi Martini; Vincentcia Chrisanta Roentoe (Universitas Pahlawan Tuanku Tambusai, 2026)
Knowledge of drug classifications and expiration dates is an essential component of safe medication use. However, awareness of these topics among school-age students still needs to be improved. This community service activity was conducted to educate students about drug logos and the importance of checking expiration dates before using medicines. The program was carried out through interactive educational sessions, discussions, and the distribution of leaflets as supporting educational materials. Participants’ knowledge was assessed using pre- and post-tests. The results demonstrated an improvement in students’ understanding after participating in the educational program. In addition, students actively engaged in the sessions and were able to answer questions related to the materials presented. The activity had a positive impact on students’ knowledge of proper medication use, highlighting the importance of implementing similar educational programs on a continuous basis to promote safe and responsible medicine use.